Application of LEAN methodology to support projects improvements in a die casting industry - Sousa, Liliana Marina Ferreira de (2018)
The main goal of this project is to define waste, measure and eliminate it, inherent to the production of aluminium die casting parts on the company Schüle Druckguss in Germany. In order to eliminate waste, a set of improvement projects were carried out focusing on the production in the different halls of the company. For that purpose, Lean thinking and tools were used as supporting methodology. It is important to highlight that these projects include issues like the organization of the workplace, the optimization of the workload for the worker, programing transport routes and minimize inventory of raw material and finish goods. Towards to achieve the previous goals, it was necessary to observe operations and procedures, measure time, detect bottlenecks or critical tasks and test different scenarios, aiming to reduce the most wasteful activities. Referring to the workplace organization, the solution achieved consists on the application of a colored marking system on the floor to define the transport way and the place for the material. Regarding the workload of the worker, it was optimized given the worker, in the new procedure, more tasks, mostly due to the introduction of automation of controlling process. About the routes for the truck coming from the daughter company in Slovakia, it was changed and some wasteful activities reduced, obtaining a minimization of 15% of the time spent on these activities per day. Note that human and material resources were also saved with the new proposal. Furthermore, the necessary quantity of inventory referent to one product was calculated the economic quantity order and minimized costs in 34%. For the finish goods it was proposed a new layout for the boxes, in order to be transported more quantities, according with customers demand. Finally, it was studied a product and its variations, that is die casted on the daughter company in Slovakia and machined in Germany, in order to change its production to a continuous line in Germany. Thus, it was included on the Die Casting Island (DCI), three external processes, minimizing the time in transportation and using fewer workers than the actual situation. The current project is focused on continuous improvement, providing a low cost approach and performs the main goal which is to achieve the best practices within the organization.